2020
DOI: 10.1002/stem.3282
|View full text |Cite
|
Sign up to set email alerts
|

MiR-184 directly targets Wnt3 in cardiac mesoderm differentiation of embryonic stem cells

Abstract: Embryonic stem (ES) cells have the property of self-renewal and multi-directional differentiation, and provide an ideal model for studying early embryo development in vitro. Wnt3, as Wnt family member 3, plays a vital role during ES cell differentiation. However, the exact regulatory mechanism of Wnt3 remains to be elucidated. MicroRNAs can directly regulate gene expression at the post-transcriptional level and play critical function in cell fate determination. Here, we found the expression level of miR-184 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…For global LVM, seventeen independent variants reached genomewide significance (Table 1), including many genes previously recognized to be associated with cardiovascular disease. BAG3, BTN3A2 and other identified variants include those previously associated with hypertrophic cardiomyopathy, restrictive cardiomyopathy, mitral valve disease, and left ventricular dilation [16][17][18][19][20][21][22][23][24][25] . GWAS of septal mass identified three unique genes (HIVEP3, ESYT3, and HMGA1) and nine genes shared with LVM.…”
Section: Genome-wide Studies Of Cmr-derived Global Lvm Apical and Sep...mentioning
confidence: 99%
“…For global LVM, seventeen independent variants reached genomewide significance (Table 1), including many genes previously recognized to be associated with cardiovascular disease. BAG3, BTN3A2 and other identified variants include those previously associated with hypertrophic cardiomyopathy, restrictive cardiomyopathy, mitral valve disease, and left ventricular dilation [16][17][18][19][20][21][22][23][24][25] . GWAS of septal mass identified three unique genes (HIVEP3, ESYT3, and HMGA1) and nine genes shared with LVM.…”
Section: Genome-wide Studies Of Cmr-derived Global Lvm Apical and Sep...mentioning
confidence: 99%
“…In the fly Drosophila, miR-184 is found with involvement in numerous biological functions, particularly female germline stem cell differentiation [36]. It is also documented with crucial roles regulating the differentiation of other types of stem cells like embryonic stem (ES) cells and periodontal ligament stem cells as well as physiological functions of granulosa cells [37][38][39]. Particularly, its function in the regulation of cell physiologic processes like neural cells' growth and differentiation may suggest therapeutic potential in human diseases [40].…”
Section: The Physiologic Functions Of Mir-184mentioning
confidence: 99%
“…miR-184, as a brain-specific miRNA, is discovered to exert pathogenic roles in Rett syndrome [59], which the disease is characterized by neuropsychiatric abnormalities [60]. miR-184 plays a substantial role in differentiating ES cells to some cardiac cells like mesoderm and cardiomyocytes by regulating Wnt3 expression [37]. The results of a cell model study have shown that inhibition of miR-184 suppressed inflammation and oxidative stress process, and as a result prevented apoptosis in cardiomyocytes [61].…”
Section: The Role Of Mir-184 In Human Diseasesmentioning
confidence: 99%
“…[4][5][6][7][8] It plays a critical role in development, cell proliferation, differentiation, oxidative modification, and regulation of cell apoptosis. [9][10][11][12] The microRNA-184 responds to and regulates animal viral infection in host cells. The expression of miR-184-3p increased after reticuloendotheliosis virus and avian leukosis virus infection in both exosomes and chick embryo fibroblast (CEF) cells.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA‐184 is a conserved miRNA with high abundance in different species 4–8 . It plays a critical role in development, cell proliferation, differentiation, oxidative modification, and regulation of cell apoptosis 9–12 . The microRNA‐184 responds to and regulates animal viral infection in host cells.…”
Section: Introductionmentioning
confidence: 99%